Parental Involvement in Education in Ghana: The Case of a Private Elementary School - Donkor, Anthony (International Journal about Parents in Education, 2023)
The author of the study reported here set out to understand and then explain the degree to which predominantly low-income, illiterate parents of children at a Ghanaian community school value education. Information gained from this exploratory study will contribute to the knowledge base on the nature of parental support — specifically, perceptions and the valuing of education in an economically developing nation in sub-Saharan Africa. The exploratory nature of this study, however, identified other factors associated with parental values and parental involvement in education that influence the nature and degree of educational support that they provide to their children, including culture, economic circumstances, priorities, self interest, parental level of education, family structure, and family size. This study raises fundamental questions about parental perceptions toward education in the Weija Community of Ghana that have relevance for other countries in Africa.